Heterogeneity in the Effect of Size on Internal Migration in the United States: A Gravity Model and PPML Estimator Approach - Nawaraj S. Paudel; Sajal Lahiri (ZBW - Leibniz Information Centre for Economics, 2024)
This paper explores the influence of economic size on inter-state migration within the USA, addressing whether people relocate from larger to smaller states and whether regional differences affect this trend. This study utilizes the structural gravity model and panel data spanning 2000 — 2017. The metrics used to gauge state size include GDP, Population, and land area. We find fairly strong support for our hypothesis that individuals are relocating from larger states to smaller ones. The impact of size on internal migration within the USA shows no distinction between the Mid-West and South regions. However, the influence of size on migration varies for the West and North-East compared to interstate migration. We carry out a series of robustness checks, and the qualitative results remain the same. Internal migration between states and regions in the USA can have significant policy implications for state and federal resource allocation, labor markets, tax revenues, economic resilience, and regional disparities.
Keywords: R23; R12; O15; 330; Inter-State Migration; Regional Migration; U.S.A.; Size; Gravity Model